2011
DOI: 10.1007/s10787-011-0092-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and treatment of Schistosoma mansoni-induced liver fibrosis in mice

Abstract: The present study was designed to examine the potential preventive and curative effects of curcumin, resveratrol, imatinib, rosiglitazone, losartan and bosentan (BOS) on Schistosoma mansoni-induced liver fibrosis in mice. Induction of liver fibrosis was produced in male Swiss mice by subcutaneous injection of S. mansoni cercariae per mouse. Mice were left for 28 days before starting the experiment then mice were divided into two main groups. The first group was further subdivided into experimental groups and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 50 publications
1
26
0
Order By: Relevance
“…We have previously demonstrated that silymarin reduces granuloma area and collagen deposition during acute S. mansoni infection (8). It has been previously demonstrated that other antioxidants also have the ability to prevent schistosomiasis-induced fibrosis when adminis- tered in the acute phase (4,5). El-Lakkany and coworkers (2012), treating infected mice with silymarin from 84 to 126 dpi, observed a slight decrease in the parasite burden and then in fibrosis, but the effect was smaller than that of praziquantel alone and possibly secondary to the decrease in burden (42).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that silymarin reduces granuloma area and collagen deposition during acute S. mansoni infection (8). It has been previously demonstrated that other antioxidants also have the ability to prevent schistosomiasis-induced fibrosis when adminis- tered in the acute phase (4,5). El-Lakkany and coworkers (2012), treating infected mice with silymarin from 84 to 126 dpi, observed a slight decrease in the parasite burden and then in fibrosis, but the effect was smaller than that of praziquantel alone and possibly secondary to the decrease in burden (42).…”
Section: Discussionmentioning
confidence: 99%
“…vitro and in prevention of fibrosis in vivo in a mouse model of schistosomiasis (9,15), showed a significant increase in release of AP (Fig. 3) and PGI (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Use of both AP and PGI as measures of drug effects on cestodes has been mostly limited to E. multilocularis (15), There are limitations in their general use. Both are pathogens of humans, and accidental injection may be infectious.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a Schistosoma mansoni-injected model, the preventive and curative effects of liver fibrosis were evaluated by using antioxidants such as resveratrol, curcumin, and N-acetylcysteine (NAC); results indicated that curcumin had potent anti-fibrotic activity in both suppressing and reversing fibrosis, whereas resveratrol had a beneficial effect only in suppressing fibrosis (El-Agamy et al 2011). In BDL-and CCl4-or TAAtreated rats, NAC prevented liver fibrogenesis associated with decreased oxidative stress in the liver (Nissar et al 2013;Yang et al 2008).…”
Section: Down-regulating Myofibroblast Activation and Ecm Productionmentioning
confidence: 99%